2017
DOI: 10.1212/wnl.0000000000004029
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament markers for ALS correlate with extent of upper and lower motor neuron disease

Abstract: This study provides Class II evidence that elevated concentrations of CSF pNfH and NfL can accurately identify patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
230
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(264 citation statements)
references
References 17 publications
29
230
5
Order By: Relevance
“…Finally, as for the power of pNfH to discriminate between ALS and HC, our results are in line with previous reports about pNfH quantifications in the serum and CSF of ALS patient using the same ELISA kit [14] or other quantification methods [6]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, as for the power of pNfH to discriminate between ALS and HC, our results are in line with previous reports about pNfH quantifications in the serum and CSF of ALS patient using the same ELISA kit [14] or other quantification methods [6]. …”
Section: Discussionsupporting
confidence: 91%
“…Correlations between neurofilaments and clinical parameters such as diagnostic latency and disease progression have been already been noted in previous studies in ALS [5, 6, 13, 14, 20]. We found that serum and CSF pNfH correlated significantly with progression rate at diagnosis and at the last observation, total ALSFRS-R score, and modified Rankin scale score at the last observation (albeit not at diagnosis).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies on ALS patients reported stable NfL levels, but showed an increase over time for a subset of patients with a rapid disease progression 17, 42, 43. Serum NfL levels have also been shown to progressively increase in sporadic PPA patients 44.…”
Section: Discussionmentioning
confidence: 96%
“…While some authors have reported an association between CSF NFs and the number of body segments showing upper and lower motor neuron involvement42 or a correlation between CSF NFL and MRI measures of degeneration of the corticospinal tract,43 our results support the view that NF levels reflect the rate of motor neuron degeneration, that is, the biological aggressiveness of the disease (and therefore the rate of clinical deterioration), rather than its anatomical extent (and the clinical stage),5 being already high in patients with recent onset of symptoms and not differing between El Escorial diagnostic categories 11. This is also in agreement with stability of serum NFL over time,18 which seems to reflect the linear progression of clinical deterioration in ALS 44.…”
Section: Discussionmentioning
confidence: 97%